The Water Management Impacts of Large-Scale Mining Operations: A Social and Environmental Perspective - Salazar-Navarrete, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This study investigates water consumption in two areas with limited water resources—the Salar de Atacama and Salar de Atacama-Vertiente Pacifico basins in Chile’s Antofagasta Region—with the aim of developing strategies that incorporate social and environmental aspects into water management. A qualitative approach was employed that involved a focus group with twelve water management representatives and surveys of the general population (468 responses). Additionally, the current state of water rights in the two basins was examined and the feasibility of the proposed strategies was assessed. The findings reveal that the mining industry’s development approach is mostly viewed as negative, mainly due to inadequate community engagement, confidential consumption data, and limited government oversight. The quantitative findings indicate that 53.8% of respondents see the main obstacle as the lack of a solution satisfying both parties. Additionally, 35.3%, 24.4%, and 22.4% believe transparency, objective information provision, and detailed resource usage disclosure by mining companies would help. Adopting a comprehensive water stewardship approach that considers social and environmental factors would enable a novel contribution to a more effective and sustainable water resource management system in northern Chile, mitigating communities’ negative perceptions of the industry and facilitating the integration of communities and involved agents. Therefore, improved management and transparent collaboration among stakeholders are essential for responsible water resource use in mining. © 2024 by the authors.